PENYULUHAN PENGUATAN LITERASI TRADISI SPIRITUAL SEBAGAI UPAYA PEMBENTUKAN IDENTITAS PSIKOLOGIS PADA MASYARAKAT SASAK DI KABUPATEN LOMBOK BARAT - Danang Nur Adiwibawa (Nusantara Hasana Journal, 2024)
Spiritual tradition literacy is the ability to understand and apply spiritual values ​​in everyday life. Spiritual literacy can be developed in various ways, including: religious approaches and spiritual practices. The psychological identity of the community can be interpreted as self-identity and social identity. Self-identity is a psychological concept related to how a person knows himself. While social identity is the knowledge possessed by a particular social community. Lombok is one of the islands in the Lesser Sunda Islands. Kuripan is one of the villages in Kuripan District, West Lombok Regency. Until now, there have been no activities that focus on strengthening spiritual tradition literacy as an effort to form psychological identity in Kuripan Village. Therefore, it is necessary to carry out community service activities in the form of counseling to strengthen spiritual tradition literacy as an effort to form psychological identity in the Sasak community in Kuripan Village, West Lombok Regency. Based on the activities, it can be seen that there is a 20% increase in community understanding of spiritual traditions and a 35% increase in community understanding that spiritual traditions can form psychological identity.